Intoleransi Pendidikan di Indonesia Menurut Pandangan Islam - Bayukarizki, Said Muammar; Soleman, Noviyanti (Sekolah Tinggi Agama Islam Babussalam Sula, 2021)
Educational intolerance in Indonesia according to Islamic perspective. Indonesia is a country that rich in culture, ethnic, linguistic and religious diversity. Recently, there was a case of religious intolerance in educational institutions. There have been frequent cases of interfaith intolerance in educational institutions. In fact, the intolerance rooted in local regulations. As muslim majority country, the case have strong relationship with Islam. The paper aims to analyse the educational intolerance in Indonesia based on Islamic perspective. By using hadith and Quran as the Islamic guidelines, the writer try to analyse the case. This qualitative research found that all the intolerance acts are prohibited in Islam. There is a hadith that strengthens it and stated that Allah SWT loves a good and tolerant religion.